Učinkovita raba virov financiranja komunalne infrastrukture za trajnostni razvoj lokalnih skupnosti - Radek, Zdenka (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The research in this paper has been undertaken from the viewpoint of problems and unresolved issues in the field of sources of financing urban infrastructure. As regards investments into urban infrastructure, individual local communities in Slovenia have been wandering about up a blind alley for years. Political interests are those that prevail once decisions have to be made on the price of public utility services, which represent an important source of financing urban infrastructure. Throughout the years, users of these services should pay the actual or justifiable costs of implementation. If they do not, future generations will bear the burden of these costs. The initial part of the paper explores the theoretical bases when searching for sources of financing urban infrastructure, while the second part presents the application utilising a concrete example of a public utility company, which implements its activity as a public utility company for the discharge and treatment of urban wastewater and rainwater in different local communities. It faces the problem whether the adoption (or failure thereof) of a political decision on the price of network charges in individual local communities will contribute to (non-) acquiring an important source of financing urban infrastructure and the consequences of this decision. One of the possible solutions is the distribution of responsibilities and authorities between the local community and the public utility company. This means that local communities should be responsible for investments into urban infrastructure and also responsible for determining the price of public utility services, including network charges. Appropriate model extraction and efficient use of sources of financing municipal infrastructure will contribute to the sustainable development of local communities, and will be useful in practice mean significant savings when investing in municipal infrastructure.
Keywords: network charges; sources of financing; public utility company